2020
DOI: 10.1093/biolre/ioaa087
|View full text |Cite
|
Sign up to set email alerts
|

Development of multipurpose technologies products for pregnancy and STI prevention: update on polyphenylene carboxymethylene MPT gel development†

Abstract: Abstract Current modern contraceptives rely heavily on the use of hormones. These birth control drug products, including pills, patches, injections, and IUDS, have been extremely beneficial to millions of women and their families over the past 50 years. But a surprisingly high number of women abandon such modern methods, many because they cannot tolerate the side effects and others because they have medical issues for which hormonal methods are contraindicated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 107 publications
(101 reference statements)
2
18
0
Order By: Relevance
“…The goal of this study was to evaluate the antiviral efficacy of PPCM against SARS-CoV-2, which would support future studies on repurposing PPCM as a prophylaxis or therapeutic antiviral treatment method via aerosol delivery against respiratory viruses. PPCM has previously demonstrated in vitro broad-spectrum activity against several sexually transmitted infections including some of viral origin such as HIV-1, HSV-1 and 2, BPV, and Ebola virus ( Chang et al, 2007 ; Escaffre et al, 2019 ; Herold et al, 2002 ; Mesquita et al, 2008 ; Weitzel et al, 2020 ; Zaneveld et al, 2002 ). In addition, PPCM toxicity studies have shown that a 4% gel formulation was safe in a vaginal irritation assay in New Zealand White rabbits ( Zaneveld et al, 2002 ), and did not cause any apparent disease in BALB/c mice ( Mesquita et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of this study was to evaluate the antiviral efficacy of PPCM against SARS-CoV-2, which would support future studies on repurposing PPCM as a prophylaxis or therapeutic antiviral treatment method via aerosol delivery against respiratory viruses. PPCM has previously demonstrated in vitro broad-spectrum activity against several sexually transmitted infections including some of viral origin such as HIV-1, HSV-1 and 2, BPV, and Ebola virus ( Chang et al, 2007 ; Escaffre et al, 2019 ; Herold et al, 2002 ; Mesquita et al, 2008 ; Weitzel et al, 2020 ; Zaneveld et al, 2002 ). In addition, PPCM toxicity studies have shown that a 4% gel formulation was safe in a vaginal irritation assay in New Zealand White rabbits ( Zaneveld et al, 2002 ), and did not cause any apparent disease in BALB/c mice ( Mesquita et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenylene Carboxymethylene (PPCM) is a mandelic acid condensation polymer under development as a multipurpose prevention technology, and has a low cost of manufacturing under different formulations ( Weitzel et al, 2020 ). PPCM has previously demonstrated microbicidal broad-spectrum activity against sexually transmitted infections in vitro and in animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, there have been attempts to develop nonhormonal vaginal MPTs. For example, Weitzel et al developed a nonhormonal MPT vaginal gel utilizing polyphenylene carboxymethylene (PPCM) [ 97 ]. PPCM is an anionic mandelic acid condensation polymer that has been demonstrated to be active against HIV-1, HSV-1, and HSV-2 [ 98 , 99 , 100 ].…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%
“…PPCM has also been shown to act as a noncytotoxic contraceptive that causes a premature loss of the sperm acrosome and does not cause epithelial surface damage unlike nonoxynol-9 [ 101 ]. The MPT formulation consisted of 4% PPCM sodium salt and excipients such as HPMC K100, xanthan gum, glycerin, methyl paraben, and propyl paraben and would be administered precoitally [ 97 ]. Only preliminary in vitro studies have been conducted to determine the contraceptive efficacy of this formulation and showed up to 80% sperm inactivation.…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%